Assessment of knowledge and practices on injection safety among service providers in east Godavari district of Andhra Pradesh - Garapati, Sridevi; Peethala, Sujatha (Indian Journal of Community Health, 2014)
Objectives: To assess the Knowledge and Practices among service providers regarding injection safety and its safe disposal in East Godavari District of Andhra Pradesh. Materials and Methods: Cross-Sectional study conducted in one year from March 2010 to February 2011 among health care providers at all levels that is Primary, Secondary and Tertiary levels of public sector selected randomly in the five revenue divisions of East Godavari District with sample size based on 4PQ/L2 formula found to be 300; Representing 30% doctors (90), 30% staff nurses (90), 30% MPHW (F) (90) and 10% Lab-Technicians(30) and data is obtained by semi- structured questionnaire; Analyzed by using SPSS software version16.0.at p<0.05 significance level. Results: In the present study knowledge of various service providers was enquired into and practices were also observed in various aspects of injection safety. Knowledge on washing hands before giving injection was 45.6% but when it comes to practice it was observed only among 18.2%; Similarly knowledge on use of hub-cutter after giving injection was found to be 33.9% but when practice of using hub-cutter was observed, it was only 20.5%; Knowledge on safe disposal of used syringes was 53.8% but the practice was found to be poor (21.7%). Similarly Knowledge on use of color coded bags according to guidelines was 65.8% but when practice was observed it is poor (20.6%). All these differences were statistically significant with p<0.05. Conclusion: In the present study Patient preference is the main indication for injection; Knowledge of universal precautions, use of needle destroyer after giving injection and correct method for final disposal of sharps was less; whereas Knowledge of complications of unsafe injections, diseases transmitted through needle stick injuries, importance of hepatitis B immunization and Post Exposure Prophylaxis was good. Unsafe practices like not washing hands, not wearing gloves, not cleaning the site of injection and touching the needle while/ before giving injection were seen. Harmful practices like recapping of needles, re-using of syringes were observed. And also disposal of injection related waste was not according to guidelines.